Media Relations PT Angkasa Pura I pada Perhelatan G20 - Christoper, Alfonsus; Oktavianti, Roswita (Prologia, 2023)
Media relations is important for an organization or company that wants to improve its image. The G20 is a multilateral cooperation forum consisting of 19 main countries and the European Union (EU) which has middle to high income classes, developing countries to developed countries. Corporate branding is a very important sector related to corporate reputation and image. Corporate branding becomes an influential thing in the information search process, where the company will give its best in obtaining results from its activities. This research uses a strategy or case study method. The data collected is data indirectly obtained through data collection techniques such as articles, books, and the internet which have relevant data in accordance with this research. PT Angkasa Pura I obtained data through interviews, observation and documentation. The results of this study are that corporate branding carried out by PT Angkasa Pura is carried out through publication through websites and social media. Apart from that, the media relations strategy is also carried out by means of media gatherings, press releases, and events. Media relations penting bagi suatu organisasi atau perusahaan yang ingin menaikkan citra. G20 adalah forum kerja sama multilateral yang terdiri dari 19 negara utama dan Uni Eropa (EU) yang memiliki kelas pendapatan menengah hingga tinggi, negara berkembang hingga negara maju. Corporate branding menjadi sektor yang sangat penting berkaitan dengan reputasi dan citra perusahaan. Corporate branding menjadi hal yang berpengaruh dalam proses pencarian informasi tersebut, dimana perusahaan akan memberikan yang terbaik dalam memperoleh hasil dari kegiatannya. Penelitian ini menggunakan strategi atau metode studi kasus. Data yang dikumpulkan merupakan data secara tidak langsung yang diperoleh melalui teknik pengumpulan data seperti artikel, buku, dan internet yang memiliki data relevan sesuai dengan penelitian ini. PT Angkasa Pura I memperoleh data dengan wawancara, observasi, dan dokumentasi. Hasil dari penelitian ini adalah corporate branding yang dilakukan PT Angkasa Pura dilakukan melalui publikasi melalui website dan media sosial. Selain itu, startegi media relations juga dilakukan dengan media gathering, press release, dan event.